Prediction the Mental Health based on Body Image Concern, Psychological Well-Being and Self-Concept among Female High School Students - Zahra Kachoei; Majid Asgharzadeh (Iranian Evolutionary Educational Psychology Journal)
Objective: The current investigation sought to elucidate the predictive relationships between mental health, body image concern, psychological well-being, and self-concept among female adolescents enrolled in high schools within Tehran's District 21. Methods: The statistical population for this investigation encompassed all female high school students attending girls' educational institutions in Tehran's District 21 during the year 2023. A sample size of 260 participants was extracted utilizing a cluster sampling methodology. For the purpose of data acquisition, this study employed the General Health Questionnaire, Body Image Concern Scale, Psychological Wellbeing Scale, and Multidimensional Self Concept Scale. To evaluate the research hypotheses, Pearson's correlation coefficient and multivariate regression analyses were implemented. Results: The findings of the investigation indicated a statistically significant negative correlation between body image concern and mental health, a significant positive correlation between psychological well-being and mental health, as well as a significant positive correlation between self-concept and mental health among female high school students. Conclusions: Collectively, the results substantiate the significance of motivational and emotional constructs in forecasting the mental health of female high school students and may offer valuable insights for developing effective interventions aimed at enhancing students' mental health.